Stomatal and trichome diversity in Senna Mill. from Bangladesh (Bangladesh Journal of Plant Taxonomy, 2014)
Foliar epidermal characters of ten species of Senna Mill. found in Bangladesh are investigated. Anisocytic, anomocytic, paracytic, tetracytic and haxacytic stomata are found across the species. Anisocytic and paracytic stomata are common in all species. In addition to anisocytic and paracytic types, anomocytic stomata are found in Senna sophera and hexacytic stomata are observed in S. auriculata. Anticlinal wall is straight in S. alata, S. hirsuta, S. occidentalis, S. siamea and S. tora, curved in S. auriculata, S. sophera and S. siamea, and undulate in S. hirsuta and S. occidentalis. Glandular trichomes are observed in S. hirsuta and S. occidentalis, while non-gladular trichomes are predominant in the remaining species.DOI: http://dx.doi.org/10.3329/bjpt.v21i1.19264Bangladesh J. Plant Taxon. 21(1): 43-51, 2014 (June)